(untitled) (Bangladesh Journal of Botany, 2008)
The genus Hypericum has attracted scientific interest worldwide in recent years, since it is a source of a variety of biologically active compounds including the phenolics. The present study was to determine ontogenetic, morphogenetic and diurnal variation of the total phenol contents in some Hypericum species growing in Turkey namely, H. nummularioides, H. hyssopifolium, H. pruinatum and H. scabrum. Plants were separated into stem, leaf and reproductive tissues, which were dried separately, and subsequently assayed for total phenol contents. Among different tissues, leaves had higher phenol contents and the highest content reached at noon in all species tested. But, ontogenetic change in the total phenol contents of whole plants varied among the species. It reached the highest level at floral budding in H. hyssopifolium and H. scabrum, at full flowering in H. pruinatum and at fresh fruiting in H. nummularioides. Â Key words: Hypericum sp., Diurnal variation, Total phenols, Phenological cycles doi:10.3329/bjb.v36i1.1547 Bangladesh J. Bot. 36(1): 39-46, 2007 (June)